Certified Teacher's Pedagogic Competence in 21st Century Skills - Santosa, Heru; Supadi; Rahmawati, Desi (Journal of Education Reseach and Evaluation, 2022)
Pedagogic competence is a special competence, which will distinguish teachers from other professions and will determine the level of success of the learning process and outcomes for students. The aim of this study is to analyse description of the pedagogic competencies of certified educators in 21st century learning, in particular regarding the pedagogic competencies of certified educators, and 21st century teacher skills. The research method used is descriptive qualitative. The research subjects is one State High School. Data collection using observation, interviews, drawing, and others. While data analysis process, researchers must pay attention to data reduction, data presentation and conclusion drawing and verification. The researcher also conducted in-depth interviews and structured interviews, structured interviews were interviews in which the problems and questions for the interview had been set by the researcher to be submitted to the informants. The results achieved are the importance of teacher certification to be carried out, the urgency of the importance of teacher certification, namely, as a requirement in teaching, standardization of professionalism, as a legal provision, professional development, and as a form of formal recognition of the teaching profession. The implications of achieving student achievement are because the learning process carried out by the teacher can run well and the transfer of knowledge to students can be right on target.